2021
DOI: 10.1097/mph.0000000000002281
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Complications During Treatment for Pediatric Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) accounts for 15% to 20% of childhood leukemias. Because of high-intensive therapy, up to 5% of patients suffer from treatment-related mortality (TRM). Abdominal complications are frequent, however, literature on this subject is sparse. We aimed to characterize severe abdominal pain (AP) and hyperbilirubinemia experienced by pediatric AML patients treated according to the Nordic Society of Pediatric Hematology and Oncology (NOPHO)-AML 2004 protocol (n=313). Patients were censored at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…It is classically characterized by transmural inflammation of the caecum and the appendix with involvement of the ascending colon and ileum in patients with severe myelosuppression. It was first described in pediatrics during the induction of leukemia [ 3 ]. The exact incidence of this manifestation is still unknown; a systematic review published in 2005 suggested an incidence of 5.6% in adults hospitalized for hematologic malignancies or under chemotherapy for solid tumors [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is classically characterized by transmural inflammation of the caecum and the appendix with involvement of the ascending colon and ileum in patients with severe myelosuppression. It was first described in pediatrics during the induction of leukemia [ 3 ]. The exact incidence of this manifestation is still unknown; a systematic review published in 2005 suggested an incidence of 5.6% in adults hospitalized for hematologic malignancies or under chemotherapy for solid tumors [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of typhlitis in pediatric AML varies in different studies between 14-38% due to varying definitions of typhlitis: clinical signs only, clinical signs plus radiology, or histopathologic confirmation [64][65][66].…”
Section: Typhlitis -Neutropenic Enterocolitismentioning
confidence: 99%